Knowledge, opinions and compliance related to the 100% smoke-free law in hospitality venues in Kampala, Uganda: cross-sectional results from the KOMPLY Project. Issue 1 (5th January 2018) - Gravely, Shannon; Nyamurungi, Kellen Namusisi; Kabwama, Steven Ndugwa; Okello, Gabriel; Robertson, Lindsay; Heng, Kelvin Khow Chuan; Ndikum, Achiri Elvis; Oginni, Adeniyi Samuel; Rusatira, Jean Christophe; Kakoulides, Socrates; Huffman, Mark D; Yusuf, Salim; et al.
Abstract : Objective: This study evaluated knowledge, opinions and compliance related to Uganda's comprehensive smoke-free law among hospitality venues in Kampala Uganda. Design: This multi-method study presents cross-sectional findings of the extent of compliance in the early phase of Uganda's comprehensive smoke-free law (2 months postimplementation; pre-enforcement). Setting: Bars, pubs and restaurants in Kampala Uganda. Procedure and participants: A two-stage stratified cluster sampling procedure was used to select hospitality sites stratified by all five divisions in Kampala. A total of 222 establishments were selected for the study. One hospitality representative from each of the visited sites agreed to take part in a face-to-face administered questionnaire. A subsample of hospitality venues were randomly selected for tobacco air quality testing (n=108). Data were collected between June and August 2016. Outcome measures: Knowledge and opinions of the smoke-free law among hospitality venue staff and owners. The level of compliance with the smoke-free law in hospitality venues through: (1) systematic objective observations (eg, active smoking, the presence of designated smoking areas, 'no smoking' signage) and (2) air quality by measuring the levels of tobacco particulate matter (PM2.5 ) in both indoor and outdoor venues. Results: Active smoking was observed in 18% of venues, 31% had visible 'no smoking' signage and 47% had visible cigarette remains. Among interviewed respondents, 57% agreed that they had not been adequately informed about the smoke-free law; however, 90% were supportive of the ban. Nearly all respondents (97%) agreed that the law will protect workers' health, but 32% believed that the law would cause financial losses at their establishment. Indoor PM2.5 levels were hazardous (267.6 µg/m 3 ) in venues that allowed smoking and moderate (29.6 µg/m 3 ) in smoke-free establishments. Conclusions: In the early phase of Uganda's smoke-free law, the level of compliance in hospitality venues settings in Kampala was suboptimal. Civil society and the media have strong potential to inform and educate the hospitality industry and smokers of the benefits and requirements of the smoke-free law.